Accessible Spaces in Inclusive Schools - María Julieta Solórzano-Salas (Universidad Nacional, Costa Rica, 2013)
This literature review is focused on physical accessibility, a basic requirement in educational institutions to ensure that all members of the education community have access to inclusive settings, where they can exercise their duties and rights by themselves. In addition, it summarizes theoretical proposals -the universal design, for instance-, which can guide staff members from these institutions and professionals related to space management, in assessing and achieving appropriate spaces.